2017
DOI: 10.5144/0256-4947.2017.216
|View full text |Cite
|
Sign up to set email alerts
|

Current umbilical cord clamping practices and attitudes of obstetricians and midwives toward delayed cord clamping in Saudi Arabia

Abstract: BACKGROUNDIn Saudi Arabia, as in many countries, there is usually no clear definition of the timing of umbilical cord clamping (UCC) in the policies and procedures used by hospitals. The World Health Organization (WHO) recommends delayed cord clamping (DCC) (>1 minute after birth) as it can significantly improve hemodynamics and long-term neurodevelopment.OBJECTIVETo investigate current practices of healthcare professionals on the timing of UCC in Saudi Arabia.DESIGNCross-sectional survey.SETTINGFive tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 19 publications
5
34
2
1
Order By: Relevance
“…For example, years of clinical experience was significantly associated with cord milking practice. (21) 108 (11) 181 (19) 101 (10) 371 (38) Resuscitation required 965 195 (20) 63 7189 (20) 169 (18) 349 (36) Shoulder dystocia 959 209 (22) 107 (11) 162 (17) 115 (12) 366 (38) Abbreviations: FHR, fetal heart rate; NA, not applicable.…”
Section: Practice Type and Provider Characteristics On Cord Milkingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, years of clinical experience was significantly associated with cord milking practice. (21) 108 (11) 181 (19) 101 (10) 371 (38) Resuscitation required 965 195 (20) 63 7189 (20) 169 (18) 349 (36) Shoulder dystocia 959 209 (22) 107 (11) 162 (17) 115 (12) 366 (38) Abbreviations: FHR, fetal heart rate; NA, not applicable.…”
Section: Practice Type and Provider Characteristics On Cord Milkingmentioning
confidence: 99%
“…Furthermore, surveys and observations of provider practice show inconsistent uptake of these evidencebased methods. [18][19][20][21][22][23] Midwifery practice of DCC in the United States was first explored by Mercer et al in 2000. 24 The authors surveyed 157 members of ACNM and found that 69% practiced DCC (36% for 1-3 minutes and 33.1% for Ͼ3 minutes).…”
Section: Introductionmentioning
confidence: 99%
“…Ülkemizde yapılan, plasenta ve umbilikal kordon hakkında verilen interaktif eğitimin etkinliğinin değerlendirildiği bir çalışmada; ebelerin plasenta ve umbilikal kordon ile ilgili bilgilerinin yeterli olmadığı, verilen eğitim ile bilgi puanlarının yükseldiği ve yenidoğana bakım veren ebelerin bilgi olarak güçlendirilmesi gerektiği sonucu çıkarılmıştır (1). Kadın doğum hekimleri ve ebelerin kordon klempleme uygulaması ve bu uygulamaya yönelik tutumlarına yönelik yapılan bir çalışmada pozitif basınçlı ventilasyon gerektiren bebekler için GKK'nin yararları konusunda daha düşük seviyelerde bir anlaşma bildirilirken, katılımcıların çoğunluğu (%69-71), GKK'nin hem term hem de preterm bebekler için faydalı olduğunu ifade etmişlerdir (46). Kanada'da yapılan bir çalışmada; kadın doğum hekimlerinin çoğunluğunun (%77,9), aile hekimlerinin %60'ının ve ebelerin %9,8'inin term bebeklerin kordonunu hemen klempleyip kestiği (<30 saniye) ve kadın doğum hekimlerinin %6,5'i, aile hekimlerinin %9,1'i ebelerin %65,7'sinin doğumdan iki dakika ya da daha fazla sonra GKK'yi uyguladıkları tespit edilmiştir.…”
Section: Sağlık Profesyonellerinin Geciktirilmiş Kordon Klempleme Uygunclassified
“…[20][21][22][23][24][25][26][27] This review aimed to answer the questions: (a) What strategies are used to implement delayed cord clamping or cord milking in different settings around the world? [20][21][22][23][24][25][26][27] This review aimed to answer the questions: (a) What strategies are used to implement delayed cord clamping or cord milking in different settings around the world?…”
mentioning
confidence: 99%
“…It is important to note that there are very limited data on rates of placental transfusion practice on a global scale, with current evidence from small published surveys and one systematic review indicating adoption of practice is poor. [20][21][22][23][24][25][26][27] This review aimed to answer the questions: (a) What strategies are used to implement delayed cord clamping or cord milking in different settings around the world? (b) What measures are taken to evaluate and improve delayed cord clamping or cord milking compliance?…”
mentioning
confidence: 99%